Guía para evaluar un programa de cumplimiento en la Nube - García Gutiérrez, Jorge Wilmar; Gómez Escallón, Juan Felipe (Universidad Antonio Nariño, 2024)
This article is designed to help the reader understand and strengthen their compliance initiatives in cloud environments. To do this, it begins with the contextualization of cloud computing, then goes deeper into the documentation related to the different components of a compliance program, as well as the challenges that companies face in its implementation, and ends with a proposal to evaluating your compliance program. This is done using the CSA cloud controls matrix and the COBIT governance framework performance management process.